COMPREHENSIVE REVIEW ON THE ROLE OF LABORATORY SPECIALISTS IN DISEASE DIAGNOSIS AND MONITORING. - FARIS SALEH MOHAMMED ZBADEEN, ABDULLAH FARIS MANA AL HAYDAR, MOHAMMED MAHDI ALSHAMLAN, MANSOUR ABDULLAH MANSOUR AL HAYDAR, MOHAMMED HAMAD NASSER ALMANSOUR, MUTEB HAMAD NASSER ALMANSOUR, (Chelonian Research Foundation, 2023)
laboratory specialists are vital in determining, treating, and framing the spine of worldwide wellbeing. This comprehensive survey looks at the different parts of restorative proficiency, covering all angles of research facility testing, innovative progress, challenges, and prospects. Through a thorough examination of the writing and current hone, this audit highlights the significance of healthcare experts giving exact and convenient care of illness movement and giving clinical direction over numerous restorative specialties. Keywords: laboratory specialists, disease diagnosis, monitoring, laboratory testing, healthcare, technological advancements